Serum anti-glycan antibodies in paediatric-onset Crohn’s disease: association with disease phenotype and diagnostic accuracy - Sładek, Małgorzata; Wasilewska, Agata; Świat, Agnieszka; Ćmiel, Adam (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Antibodies reacting with various microbial epitopes have been described in inflammatory bowel disease (IBD) and are associated with a specific diagnosis and clinical presentation. Aim: To evaluate the profile of new anti-glycan antibodies, their potential association with disease phenotype and diagnostic accuracy in paediatric Crohn’s disease (CD). Material and methods: Blood samples from 134 paediatric IBD patients (109 CD, 25 ulcerative colitis (UC)) and 67 controls were blindly analysed for anti-Saccharomyces cerevisiae (ASCA), anti-chitobioside carbohydrate (ACCA), anti-laminaribioside carbohydrate (ALCA), and anti-mannobioside carbohydrate (AMCA) antibodies using commercially available assays. The serological response to glycans was correlated with clinical disease characteristics. Results : At least one of the tested anti-glycan antibodies was present in 75% of CD patients. Despite the high frequency of reactivity to glycan epitopes, a limited overlap of serological markers was observed. In total, 49% of ASCA-negative patients presented with one of the following: ACCA, ALCA, or AMCA. The occurrence of one antibody from the anti-glycan panel was independently associated with complicated disease phenotype and ileocolonic disease location. A higher level of immune response as assessed by the quartile sum scores for ACCA, ALCA, and AMCA was linked with older age at diagnosis (10–17 years) and ileocolonic disease location. The ASCA had the greatest accuracy for diagnosis and differentiation of CD. Conclusions : Qualitative and quantitative serologicalal response to glycan epitopes was associated with distinct clinical presentation in paediatric CD patients. This raises the possibility for the use of these markers to differentiate subgroups of CD patients with more sever clinical presentation. The ASCA was the most accurate serological marker for CD; however, testing for the new anti-glycan antibodies may constitute an adjunctive tool in a specific group of patients to aid in the differentiation of CD with absent ASCA from ulcerative colitis.